2010
DOI: 10.1021/jo1012493
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Anticancer Activities of (−)- and (+)-Thespesone

Abstract: The natural p-naphthoquinone (-)-thespesone 1 and its (+)-enantiomer were synthesized for the first time by bisacylation of a 5-lithiodihydrobenzofuran 2' with 4-methyl-3-tert-butoxycyclobut-3-ene-1,2-dione 3. The racemate of the required 2-arylpropan-1-ol precursor 10 was kinetically resolved by an enzyme-catalyzed acetylation exclusively of the (S)-enantiomer. Saponification of this acetate mediated by the same enzyme, porcine pancreas lipase (PPL), afforded the (S)-2-arylpropan-1-ol in 96% ee. Its unreacted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The tricyclic ring system of 1 was assembled by coupling a squaric acid precursor 3 with the brominated dihydrobenzofuran 2 (Figure 1), which, in turn, was prepared in eight steps in 8.3 % overall yield. [7] Asymmetric hydrogenation provides an attractive, very direct route to enantioenriched tetrahydrofurans and dihydrobenzofurans from aromatic precursors, which are, in general, easily accessible. For example, the reported synthesis of 1 could be considerably shortened by using enantioselective hydrogenation for the introduction of the stereocenter in precursor 2.…”
Section: Introductionmentioning
confidence: 99%
“…The tricyclic ring system of 1 was assembled by coupling a squaric acid precursor 3 with the brominated dihydrobenzofuran 2 (Figure 1), which, in turn, was prepared in eight steps in 8.3 % overall yield. [7] Asymmetric hydrogenation provides an attractive, very direct route to enantioenriched tetrahydrofurans and dihydrobenzofurans from aromatic precursors, which are, in general, easily accessible. For example, the reported synthesis of 1 could be considerably shortened by using enantioselective hydrogenation for the introduction of the stereocenter in precursor 2.…”
Section: Introductionmentioning
confidence: 99%
“…The first successful synthesis of natural p-napthoquinone (-) thespesone (compound 6) and its enantiomer was performed by Breyer et al (2010). These investigators also screened its anticancer activity and found (-) thespesone to be more efficacious against a group of six cancer cell lines along with multi-resistant cell lines than TQ and its enantiomer.…”
Section: Analogs Of Tqmentioning
confidence: 99%
“…[20] The silanes 4 were additionally functionalized to form chiral five-membered silyl rings (6) without loss of enantioselectivity using iridium-catalyzed intramolecular dehydrogenation. [21] We determined the absolute configuration of hydrosilylation products by X-ray analysis of the compounds 6 b and 6 v. [22] The phenol derivatives with chiral motifs at the ortho-position are also core structures and useful precursors [23] for bioactive natural products, [24] and 7 b was obtained in 86 % yield by oxidative hydrolysis [20] of the cyclic silane 6 b. Chiral 3-substituted 2,3dihydrobenzofurans [25] are precursors for the anticancer active (À)-thespesone [26] or single-stranded abiotic metallofoldamers. [27] (S)-(+)-3-Methyl dihydrobenzofuran (8 b) was obtained through an intramolecular Mitsunobu reaction [20] of 7 b in 62 % yield (the product was highly volatile).…”
mentioning
confidence: 99%